Enhancing Technology-Based Financial Literacy among Textile MSMEs in Padang City through SIAPIK Application Training - Yosi Suryani; Nurhayati; Rahmat Eka Putra; Yudhytia Wimeina (Warta Pengabdian Andalas, 2026)
Good financial management is a crucial factor in supporting the sustainability of micro, small, and medium enterprises (MSMEs). However, many MSMEs still face challenges in maintaining systematic bookkeeping, particularly in the textile industry. This Community Service activity aims to improve MSMEs' financial and digital literacy through training and mentoring in the use of the Sistem Informasi Aplikasi Pencatatan Informasi Keuangan (SIAPIK). The activity was held in Padang City and involved 10 MSME participants. The activity's implementation method included preparation, outreach, hands-on training, mentoring, and monitoring and evaluation. The results showed that 90% of participants successfully adopted the SIAPIK application, 80% were able to record transactions consistently, and produce simple financial reports. Furthermore, participants exhibited a substantial improvement in their understanding following the training, as evidenced by the marked increase in average pre- and post-test scores. This activity has proven effective in improving MSMEs' digital financial management skills. However, challenges remain in consistent application use, influenced by digital literacy levels and manual record-keeping habits. Therefore, ongoing support is needed to ensure that the implementation of the SIAPIK application can run optimally and sustainably.